2012
DOI: 10.16910/jemr.5.4.4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotional picture thematic content on exploratory eye movements

Abstract: In picture viewing, emotional vs. neutral stimuli could play a different role in eye movement parameters and in the spatial progression of the scanpath. The aim of this paper is to investigate exploratory behaviour of normal subjects during the vision of emotional vs. non-emotional stimuli, by considering to what extent the thematic content (animate vs. inanimate) is likely to influence the observer’s eye movements. Sixty-five subjects’ eye movement patterns were measured while looking to emotional (pleasant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Object / Recipient, Patient / Inactive participant, Facial movements of participant, Author / Speaker lower the gaze costs. These results do partially correlate with the results reported in [3,4,5,23,25]; however, we revealed that dynamicity, interactionality, emotionality produce steady negative and positive gaze effects in Text AOIs in cross-modal switches, whereas in monomodal switches referent prominence and space location were most counted. Additionally, fictionality revealed in [6,27] is not found as potent in the attested stimuli.…”
Section: Gaze Behavior As Affected By Event Construal In Text Aoissupporting
confidence: 90%
See 1 more Smart Citation
“…Object / Recipient, Patient / Inactive participant, Facial movements of participant, Author / Speaker lower the gaze costs. These results do partially correlate with the results reported in [3,4,5,23,25]; however, we revealed that dynamicity, interactionality, emotionality produce steady negative and positive gaze effects in Text AOIs in cross-modal switches, whereas in monomodal switches referent prominence and space location were most counted. Additionally, fictionality revealed in [6,27] is not found as potent in the attested stimuli.…”
Section: Gaze Behavior As Affected By Event Construal In Text Aoissupporting
confidence: 90%
“…In recent years, eye-tracking research in cross-modal (for instance, in text and image) and monomodal switches has become an integral component of usability multimedia and VR studies. Gaze costs are explored as contingent on 1) foregrounding effects in pictorial modality [8,33] or language modality [2,8,14,30], 2) spatial effects in bimodal systems [18,23,25], 3) types of tasks performed [4,12,24], 4) several cognitive foregrounding effects, for instance dynamicity and agentivity [28,35], 5) cross-modal information mapping [1,30,37]. Although prognostic computing has made significant progress, there are still challenges for assessing gaze effects in monomodal and bimodal systems as affected by systemic event construal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, effects of ANIM on word order in naming two pictures in a conjoined noun phrase could be due to visual salience. In an eye tracking study, Carniglia, Carputi, Manfredi, Zambarbieri, and Pessa (2012) showed that there is a bias for fixations to pictures with animate referents compared to those with inanimate referents. The former were earlier, longer, and more often fixated than the latter.…”
Section: Semantic and Rhythmic Constraints And The Scope Of Speech Planningmentioning
confidence: 99%
“…Although the special role of negatively valenced stimuli (e.g., snakes) has been put forward (e.g., Fox et al, 2000;Yiend and Mathews, 2001;Calvo et al, 2006), the majority of results rather supports the existence of arousal-driven, valence-independent effects. Hence, emotional compared to neutral stimuli were found to initially attract and maintain attentional processes (Calvo and Lang, 2004;Calvo and Avero, 2005;Nummenmaa et al, 2006;Carniglia et al, 2012).…”
Section: Emotion In Picture Viewingmentioning
confidence: 97%